Testing Computer Models Predicting Human Responses to a High-Salt Diet - Kurtz, Theodore W; DiCarlo, Stephen E; Pravenec, Michal; Ježek, Filip; Šilar, Jan; Kofránek, Jiří; Morris, R Curtis (Hypertension (Dallas, Tex., 2018)
Recently, mathematical models of human integrative physiology, derived from Guyton's classic 1972 model of the circulation, have been used to investigate potential mechanistic abnormalities mediating salt sensitivity and salt-induced hypertension. We performed validation testing of 2 of the most evolved derivatives of Guyton's 1972 model, Quantitative Cardiovascular Physiology-2005 and HumMod-3.0.4, to determine whether the models accurately predict sodium balance and hemodynamic responses of normal subjects to increases in salt intake within the real-life range of salt intake in humans. Neither model, nor the 1972 Guyton model, accurately predicts the usual changes in sodium balance, cardiac output, and systemic vascular resistance that normally occur in response to clinically realistic increases in salt intake. Furthermore, although both contemporary models are extensions of the 1972 Guyton model, testing revealed major inconsistencies between model predictions with respect to sodium balance and hemodynamic responses of normal subjects to short-term and long-term salt loading. These results demonstrate significant limitations with the hypotheses inherent in the Guyton models regarding the usual regulation of sodium balance, cardiac output, and vascular resistance in response to increased salt intake in normal salt-resistant humans. Accurate understanding of the normal responses to salt loading is a prerequisite for accurately establishing abnormal responses to salt loading. Accordingly, the present results raise concerns about the interpretation of studies of salt sensitivity with the various Guyton models. These findings indicate a need for continuing development of alternative models that incorporate mechanistic concepts of blood pressure regulation fundamentally different from those in the 1972 Guyton model and its contemporary derivatives.
Keywords: kuchyňská sůl; cardiac output; Humans; Hypertension; modely kardiovaskulární; Computer Simulation; Models, Cardiovascular; Cardiac Output; lidé; minutový srdeční výdej; hypertension; sodium chloride; počítačová simulace; krevní tlak; Sodium Chloride, Dietary; hypertenze; blood pressure; hemodynamika; vascular resistance; Hemodynamics; Blood Pressure